Critical Discourse Analysis of the Role of Mass Media in the Cancellation Policy of Hajj Pilgrims during the Pandemic - Rohmanur Aziz (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2021)
This study aims to reveal the role of the media in disseminating information regarding the cancellation of the departure of pilgrims from the critical discourse dimensions. Therefore, this research method uses Critical Discourse Analysis from Norman Fairclough. The results of this study indicate that the role of the media in the cancellation policy of Hajj pilgrims in 2021 consists of three essential things. First, the media sided with the news content about the cancellation of the hajj based on norms by the law and various derivative regulations. Second, the mainstream media group has its concept in understanding how to disseminate the information so that it can become a public discourse and understand the public after being back on the mainstream media stage. Third, the media behaves like a ‘pendulum’ that can go back and forth to contribute to